Studying vessel biographies from the Heuneburg: an experimental approach - van Gijn, Annelou; Jacobs, Loe; Groat, Nicholas; Koning, Nicole; Braekmans, Dennis; Verbaas, Annemieke (Sidestone Press, 2019)
In the context of the BEFIM project (“Meanings and Functions of Mediterranean Imports in Early Iron Age Central Europe”) the life history of (drinking) vessels from the Early Celtic hillfort settlements of the Heuneburg was examined, studying the way of production and use. In order to do so, we set up an extensive experimental program of dozens of experiments directed at a better understanding of the way this pottery was made and used. The participation of an experienced potter allowed us to reproduce exact replicas of the supposed drinking ware and explore in detail the traces of production and the effect of temper, baking temperature and so forth on the development of production traces and wear. Especially variations in the temper material, like the frequently observed addition of calcite in the archaeological pottery, strongly affected the characteristics of the use-wear marks that developed from the preparation of different products (grape wine, honey wine, different kinds of porridge etc.). The influence of alcohol production, including fermentation, on the pottery was explored. We also tested the effect of different gestures of preparing food and drink (mixing, stirring, pounding), different ways of storage and handling, and the manner of consumption like decanting using various kinds of utensils. The traces we observed on the experimental vessels, using an integrated low and high power approach, formed the basis for our interpretation of the archaeological vessels from the Heuneburg.
Keywords: experiment; pottery function; microwear analysis; drinking habits; manufacturing traces; Early Celtic pottery